PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA MANDOR KEBUN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Prakasa Hernanta; Dwi Ratmawati (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Introduction: This study aimed to analyze the influence of leadership styles and organizational culture on the performance of plantation foremen as the first responsible person in the field with job satisfaction as an intervening variable. Methods: To examine these issues, a questionnaire distributed at 35 plantation foreman Semboro Sugar Factory. The collected data is then analyzed using the technique of partial least squares analysis using smartPLS 2.0. Results: Indicated that leadership style is positively and significantly affect performance. Organizational culture is also positive and significant effect on performance. Leadership style is positively and significantly affect performance either directly or indirectly through job satisfaction, and organizational culture in a positive and significant effect on performance, both directly and indirectly through job satisfaction. Conclusion and suggestion: Managerial suggestion is to apply nurturant leadership style and task oriented style. More is to creat and maintain the plantation foreman involvement in the culture of the organization, in line with the giving level of job satisfaction perceived by the plantation foreman that will ultimately improve the performance of the plantation foreman hopes of reaching the production of sugarcane per hectare according to the potential of existing varieties